Zero Knowledge Protocol In Cryptography - Yamini Sharma, Kawaljit Kaur, Rajwant Kaur (International Journal of Advanced Science and Technology, 2020)
This paper presents the concepts of cryptography, its features and the protocols used for havingthe stable communication focusing on zero- knowledge protocol and its benefits. Zero-knowledgeprotocols offer a new fundamental structure for digital signature and also for message authentication.It is safe and secure against flexible chosen message attack with stronger properties than the previousprotocols. The zero-knowledge signature cannot be forged against adaptive chosen-message attacks.